2015
DOI: 10.1111/1365-2664.12562
|View full text |Cite|
|
Sign up to set email alerts
|

Global analysis of seagrass restoration: the importance of large‐scale planting

Abstract: Summary1. In coastal and estuarine systems, foundation species like seagrasses, mangroves, saltmarshes or corals provide important ecosystem services. Seagrasses are globally declining and their reintroduction has been shown to restore ecosystem functions. However, seagrass restoration is often challenging, given the dynamic and stressful environment that seagrasses often grow in. 2. From our world-wide meta-analysis of seagrass restoration trials (1786 trials), we describe general features and best practice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
350
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 371 publications
(421 citation statements)
references
References 40 publications
9
350
1
2
Order By: Relevance
“…In addition, planting a high number of seeds over large spatial scales may also increase the chances of survival by temporarily overwhelm seed predators. This is partly supported by a recent review of restoration studies that found higher survival and growth of plants when a higher number of shoots/seeds were planted [62]. …”
Section: Discussionmentioning
confidence: 77%
“…In addition, planting a high number of seeds over large spatial scales may also increase the chances of survival by temporarily overwhelm seed predators. This is partly supported by a recent review of restoration studies that found higher survival and growth of plants when a higher number of shoots/seeds were planted [62]. …”
Section: Discussionmentioning
confidence: 77%
“…Seagrass restoration projects globally have had variable levels of success (van Katwijk et al . ). Restoration efforts need to be better informed to maximize benefits and avoid misplaced action, and guidance is required to strategically direct restoration activity (van Katwijk et al .…”
Section: Strategies For Actionmentioning
confidence: 97%
“…With regards to marine macrophytes, the concept of assisted migration is not new. Reforestation of seagrass meadows, which are experiencing widespread global habitat loss from a multitude of stressors (Orth et al 2006), has been attempted many times, although only ~37% of restorations have been successful (Katwijk et al 2016). Examples from seaweeds are distinctly lacking which may be due to the inherent logistical challenges associated with transplanting and maintaining seaweeds on rocky reefs, often in highly dynamic environments.…”
Section: Significance and Limitation Of Findingsmentioning
confidence: 99%